Quantitative longitudinal T2* mapping for assessing placental function and association with adverse pregnancy outcomes across gestation. - Matthias C Schabel; Victoria H J Roberts; Karen J Gibbins; Monica Rincon; Jessica E Gaffney; Aaron D Streblow; Adam M Wright; Jamie O Lo; Byung Park; Christopher D Kroenke; Kathryn Szczotka; Nathan R Blue; et al. (PLoS ONE, 2022)
Existing methods for evaluating in vivo placental function fail to reliably detect pregnancies at-risk for adverse outcomes prior to maternal and/or fetal morbidity. Here we report the results of a prospective dual-site longitudinal clinical study of quantitative placental T2* as measured by blood oxygen-level dependent magnetic resonance imaging (BOLD-MRI). The objectives of this study were: 1) to quantify placental T2* at multiple time points across gestation, and its consistency across sites, and 2) to investigate the association between placental T2* and adverse outcomes. 797 successful imaging studies, at up to three time points between 11 and 38 weeks of gestation, were completed in 316 pregnancies. Outcomes were stratified into three groups: (UN) uncomplicated/normal pregnancy, (PA) primary adverse pregnancy, which included hypertensive disorders of pregnancy, birthweight <5th percentile, and/or stillbirth or fetal death, and (SA) secondary abnormal pregnancy, which included abnormal prenatal conditions not included in the PA group such as spontaneous preterm birth or fetal anomalies. Of the 316 pregnancies, 198 (62.6%) were UN, 70 (22.2%) PA, and 48 (15.2%) SA outcomes. We found that the evolution of placental T2* across gestation was well described by a sigmoid model, with T2* decreasing continuously from a high plateau level early in gestation, through an inflection point around 30 weeks, and finally approaching a second, lower plateau in late gestation. Model regression revealed significantly lower T2* in the PA group than in UN pregnancies starting at 15 weeks and continuing through 33 weeks. T2* percentiles were computed for individual scans relative to UN group regression, and z-scores and receiver operating characteristic (ROC) curves calculated for association of T2* with pregnancy outcome. Overall, differences between UN and PA groups were statistically significant across gestation, with large effect sizes in mid- and late- pregnancy. The area under the curve (AUC) for placental T2* percentile and PA pregnancy outcome was 0.71, with the strongest predictive power (AUC of 0.76) at the mid-gestation time period (20-30 weeks). Our data demonstrate that placental T2* measurements are strongly associated with pregnancy outcomes often attributed to placental insufficiency. Trial registration: ClinicalTrials.gov: NCT02749851.